Remittance Practices and Transnational Social Spaces of Tamils and Somalis in Norway - Sarvendra Tharmalingam (Nordic Journal of Migration Research, 2011)
The aim of the article is to map the remittance practices of two war-torn migrant communities, Tamils and Somalis in Norway, by taking into account the motives behind and the purpose of the remittances. In an age of diaspora and transnational communities, where the lives of immigrants are organised beyond the boundaries of nation-states, remittance practices have been shaped by the transnational social spaces. This article takes the transnational social spaces suggested by Faist (2000a, b), namely transnational kinship groups, transnational circuits and transnational communities as its theoretical departure. Five categories of remittances are common among Tamils and Somalis living in Norway: family, politics, welfare, network and investment remittances. These categories have links with different types of transnational social spaces.